CERTIFICATIONS CALIBRATE THE CALIBRE OF THE STUDENTS - Venkata Ramana Manipatruni; Dr.Sujani Tata; Ananda Rao Bonthu (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
We aspire to be a teacher, a scholar, a scientist or even an ardent learner, whatever our aspiration might be, we usually keep watching conference presentations, attending workshops, reading news, and journal articles in order to craft our art, in other words, which we describe as the development of language teaching and promotion of language acquisition. But for a student, the means of learning a second language are manifold and all he/she needs to acquire is their serious engagement with rapt attention both inside and outside the classroom. As learning language is a natural process, first one needs to be surrounded by the language to acquire and develop any unknown language. But it’s equally noticeable that a few technical tools working based on Artificial Intelligence would also help the students learn a second language (English) better in due course of learning. Transcending the traditional and old-fashioned techniques that don’t intrigue students’ learning any longer, Our paper proposes various language development techniques and technical tools that help students acquire the second language quicker and better and subsequently develop it to the maximum extent with utmost accuracy. It also discusses various internationally acclaimed certifications like Business English Certificate (BEC) conducted by Cambridge English, Global English Testing Services (GETS HE), by Qualifications and Assessments and International and such certifications for improving the second language that helps students become proficient in the second language and competent in the workplace.